Perancangan Desain Sistem Basis Data Pengelolaan Aset: (Studi Kasus Universitas Galuh) - Dadan Mulyana; Maulana Sidiq (Jurnal Sistem Informasi Galuh, 2023)
Galuh University is a private university that has 7 faculties, 1 Postgraduate Program, Institute for Research and Community Service (LPPM), Internal Quality Assurance Agency (BPMI), Libraries and Cooperation Offices. Of the many places in Galuh University, it becomes a problem that must be faced in asset management. The management of these assets still relies on the role of humans who cannot collect a lot of asset data. If the person forgets it will be a problem especially regarding the type of asset that makes the payment and if it is late, it will be subject to sanctions or fines. This research is to make it easier to calculate the number of assets and record the maintenance of these assets. This asset management application will be web-based using the PHP programming language and MySQL as the database. The results of this study are in the form of a database design which will later be implemented on a website that can be accessed by asset managers who will record asset maintenance and also as a reminder of asset maintenance at Galuh University